Anal function in geriatric patients with faecal incontinence. Issue 9 (September 1989) - Barrett, J A; Brocklehurst, J C; Kiff, E S; Ferguson, G; Faragher, E B
Abstract : The association of faecal incontinence with constipation and confusion in the elderly is well recognised but the anal function of faecally incontinent geriatric patients is poorly understood. Anal studies were therefore performed on 99 geriatric patients (49 with faecal incontinence, 19 continent patients with faecal impaction and 31 geriatric control patients with normal bowel habit) and 57 younger healthy control patients. An age related reduction in anal squeeze pressure but not resting pressure was identified. A reduction in anal resting pressure was detected in the faecally incontinent geriatric patients but squeeze pressure did not differ significantly from that found in the other geriatric patients. Anal sensation was impaired in the faecally incontinent patients. No difference was found between the groups as measured by pudendal nerve terminal motor latency. Gross neuropathy of the distal part of the pudendal nerve does not account for the observed external anal sphincter weakness in geriatric patients or for their faecal incontinence. Internal anal sphincter dysfunction is an important factor in faecal incontinence in the elderly.